Costa Rica : Request for Stand-By Arrangement; Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Costa Rica. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses the request from Costa Rica for a Stand-By Arrangement (SBA). The program seeks to enable an orderly adjustment of the Costa Rican economy to an adverse external environment, while mitigating its adverse effects on growth and household incomes. To strengthen the external position, the authorities have tightened monetary conditions and increased exchange rate flexibility. Fiscal policy will be geared toward mitigating the impact of the adjustment on domestic activity and the most vulnerable population. IMF financial support is intended to bolster investor confidence in the authorities' policy framework.